An Investigation into Burnishing of Hollow Cylindrical Parts - et al., Ayman A. Abd-Eltwab (International Journal of Advanced Science and Technology, 2020)
Metal spinning is one of the oldest methods of chip-less formation. Metal spinning is the technique to produce axisymmetric part or component over rotating mandrel with the help of rigid tool known as roller. Conventional sheet spinning has a significant negative impact on surface quality of product items. Burnishing process is surface finishing processes to improve surface quality. In the present work a novel tool combining the two processes of conventional spinning with burnishing in the same stroke. The novel tool consists of two rollers performing the conventional spinning followed by two balls to perform the burnishing process. The set of two rollers and two balls is mounted on jaws of lathe chuck which working as a holder for the tool parts. The experimental work was conducted in order to test the proposed tool and investigate the effect of the mandrel rotational speed, the feed rate, and the burnishing force on the process load and the product quality. The Experimental results was conducted and approved the success of the presented technique. Also, the rotational speed and feed rate affected the product quality and the required load. The burnishing spring force has an optimum value of 25 kgf.